Niger Service Delivery Indicators : Education 2015 - World Bank (Washington, DC, 2017)
This report presents the results of the Service Delivery Indicators in the education sector in Niger in 2015. Survey implementation was preceded by extensive consultation with Government and key stakeholders on survey design, sampling, and adaptation of survey instruments. Pre-testing of the survey instruments took place in 2013, while training of field staff and field work took place in 2015, and data entry, cleaning, and analysis took place in 2016 and 2017. Information was collected from 256 primary schools, 1,748 teachers, and 3,661 grade four and five pupils in Niger. The results provide a representative snapshot of primary education service delivery in Niger. The survey provides information on four elements of service delivery: measures of (i) teacher effort; (ii) teacher knowledge and ability; (iii) the availability of key inputs and infrastructure; and (iv) management, supervision, and community engagement.